The antiviral mechanism of viperin and its splice variant in spring viremia of carp virus infected fathead minnow cells. Issue 86 (March 2019) - Wang, Fang; Jiao, Houqi; Liu, Wanmeng; Chen, Bo; Wang, Yeda; Chen, Buxin; Lu, Yuanan; Su, Jianguo; Zhang, Yongan; Liu, Xueqin
Abstract: Viperin is known to play an important role in innate immune and its antiviral mechanisms are well demonstrated in mammals. Fish Viperin mediates antiviral activity against several viruses. However, little has been done to the underlying mechanism. Here, we discovered a novel Viperin splice variant named Viperin_sv1 from viral-infected FHM cells. Spring varimia of carp virus (SVCV) was able to increase the mRNA levels of both Viperin and Viperin_sv1, while poly(I:C) only has effect on Viperin. Viperin functions as an antiviral protein at 24 h post-SVCV infection, but the antiviral activity dramatically declined at late infection stages. However, Viperin_sv1 inhibited SVCV replication significantly at all the tested time. Viperin_sv1, but not Viperin can facilitate the production of type I IFN and IFN stimulate genes (ISGs) through activation of RIG-1, IRF3 and IRF7 signaling cascades. On the other hand, SVCV down-regulated Viperin_sv1 at the protein level through the proteasome pathway to keep itself away from the immune system monitoring. Taken together, these findings provide new insights into the regulation of Viperin from the posttranscriptional modification perspective and the role of splicing variant Viperin_sv1 in virus-host interaction. Highlights: SVCV was able to increase the alternative splicing of Viperin. Splice variant Viperin_sv1 has more persistent effect than Viperin on antiviral responses. Viperin_sv1 facilitated the production of IFN and ISGsthrough the RIG-1, IRF3 and IRF7 signaling cascades. SVCV down-regulated Viperin_sv1 at the protein level through the proteasome pathway to evade its antiviral effect.